Secondary School Students’ Anxiety in Read-Answer-Discuss-Explain-Create Model with English as Medium Instruction in Science Class - Sukardi, Rendi Restiana; Thien, Lei Mee; Sopandi, Wahyu; Ismail, Ismail (Universitas Negeri Semarang, 2025)
This study examines the effectiveness of the Read–Answer–Discuss–Explain–Create (RADEC) model, integrated with English as a Medium of Instruction (EMI), in reducing science learning anxiety among secondary school students. The research addresses a common challenge faced by non-native English speakers in science classrooms—language-induced anxiety that hinders conceptual understanding and communication. Employing a convergent mixed-methods design, the study involved 30 secondary students purposively selected from Bandung, Indonesia. Quantitative data were collected through a time-series experiment, while qualitative insights were obtained via in-depth interviews. After five months of implementing the RADEC model with EMI, students exhibited marked reductions in communication apprehension, fear of negative evaluation, and test anxiety. At the same time, they demonstrated enhanced conceptual mastery and confidence in English-mediated scientific communication. The findings suggest that the RADEC model with EMI provides a structured yet flexible pedagogical framework, enabling pupils to access, discuss, and present scientific content in English without fear of linguistic penalties. The novelty of this study lies in its integration of a culturally responsive pedagogical model (RADEC) with EMI to address both cognitive and affective barriers in science education. This approach offers scalable potential for EMI-based instruction in multilingual, cross-national educational contexts.